A Tale of Two Capitals: How Task-Oriented and Guanxi-Oriented Psychological Capitals Lead to a Sustainable Workforce in Rural China - Xu, Chunyan; Wei, Dawei; Liu, Jintao; Zhou, Jiaxian (Frontiers in Psychology, 2021)
Psychological capital (PsyCap) is documented to be positive in influencing employees’ behavior. However, little attention has been paid to its role in maintaining a sustainable workforce in underprivileged rural areas. Also less known is the complex relations between PsyCap and other consequence variables. Moreover, previous studies in this field did not adequately address the cross-cultural applications of positive resources, though many facets of psychological capital are culture related. To address the gaps, the current study explored the complex relationships linking PsyCap and organizational commitment in a sample of public civil servants (gongwuyuan cadres, n = 583) at the township level in the rural areas of northwestern China. Two types of PsyCap, task-oriented PsyCap, which is similar to the PsyCap in the west, and guanxi-oriented PsyCap, which is unique in the Chinese culture, were measured. Task-oriented PsyCap is composed of enterprise-diligence, resiliency-perseverance, optimism-hope, and confidence-courage. Guanxi-oriented PsyCap is composed of toleration-forgiveness, modesty-prudence, thanksgiving-dedication, and respect-courtesy. AMOS 23.0 software was used to establish structural equation models (SEM). The results show that both types of PsyCap were positive predictors of organizational commitment. Vocational identity and job satisfaction mediated the relation between task-oriented PsyCap/guanxi-oriented PsyCap and organizational commitment. The chained relationship from the two types of PsyCap to vocational identity, job satisfaction and organizational commitment was also significant. These results and their implications for workforce stability are discussed.